Intense Seismicity During the 2014–2015 Bárðarbunga‐Holuhraun Rifting Event, Iceland, Reveals the Nature of Dike‐Induced Earthquakes and Caldera Collapse Mechanisms. Issue 8 (5th August 2019) - Ágústsdóttir, Thorbjörg; Winder, Tom; Woods, Jennifer; White, Robert S.; Greenfield, Tim; Brandsdóttir, Bryndís
Abstract: Over 2 weeks in August 2014, magma propagated 48 km laterally from Bárðarbunga volcano before erupting at Holuhraun for 6 months, accompanied by collapse of the caldera. A dense seismic network recorded over 47, 000 earthquakes before, during, and after the rifting event. More than 30, 000 earthquakes delineate the segmented dike intrusion. Earthquake source mechanisms show exclusively strike‐slip faulting, occurring near the base of the dike along preexisting weaknesses aligned with the rift fabric, while the dike widened largely aseismically. The slip sense of faulting is controlled by the orientation of the dike relative to the local rift fabric, demonstrated by an abrupt change from right‐ to left‐lateral faulting as the dike turns to propagate from an easterly to a northerly direction. Around 4, 000 earthquakes associated with the caldera collapse delineate an inner caldera fault zone, with good correlation to geodetic observations. Caldera subsidence was largely aseismic, with seismicity accounting for 10% or less of the geodetic moment. Approximately 90% of the seismic moment release occurred on the northern rim, suggesting an asymmetric collapse. Well‐constrained focal mechanisms reveal subvertical arrays of normal faults, with fault planes dipping inward at ∼60° ± 9°, along both the north and south caldera margins. These steep normal faults strike subparallel to the caldera rims, with slip vectors pointing toward the center of subsidence. The maximum depth of seismicity defines the base of the seismogenic crust under Bárðarbunga as 6 km below sea level, in broad agreement with constraints from geodesy and geobarometry for the minimum depth to the melt storage region. Key Points: Dike induces strike‐slip faulting in rift fabric, with fault slip direction governed by orientation of faults with respect to dike opening Caldera seismicity reveals piecemeal trapdoor‐style (asymmetric) collapse accommodated by normal faulting on multiple inward‐dipping faults Caldera collapse seismicity occurs primarily 2–8 km below surface, indicating the upper limit for a magma reservoir